Development Of Writing Learning Videos For Elementary School Students - Wiratsari, Kadek Tatanika; Margunayasa, I Gede; Wibawa, I Made Citra (Jurnal Ilmiah Sekolah Dasar, 2021)
Low-grade students still have difficulty in writing. Writing delays can hinder the learning process. This study aimed to develop writing learning video products for first-grade elementary school students whose validity has been tested. This research refers to the ADDIE development model procedure. However, this study did not implement and evaluate stages due to limited time, effort, resources, and finance. The subjects of this study were two material experts, two media experts, and two practitioners. The object of this research is the validity of the writing learning video. The data collection of this research used a questionnaire method by providing assessment sheets to two media expert lecturers, two material expert lecturers, and two first-grade elementary school teachers. The data from the validation results from the experts were then analyzed using the mean formula to determine the average validity score of the writing learning videos. The analysis results showed that the average validation score for writing learning videos is 4.44 with very good criteria. The average score of validation for writing learning video materials is 4.06 with very good criteria. Based on the analysis results, the writing learning video for first-grade students of SD was declared valid and had very good criteria.